Poisson-Schrödinger simulation and analytical modeling of inversion charge in FDSOI MOSFET down to 0 K – Towards compact modeling for cryo CMOS application. (December 2021) - Aouad, M.; Poiroux, T.; Martinie, S.; Triozon, F.; Vinet, M.; Ghibaudo, G.
Abstract: Poisson-Schrödinger (PS) simulations and an analytical charge model for a back biased FDSOI structure operated at deep cryogenic temperatures have been developed. PS simulations have been conducted down to 0 K, where metallic statistics applies, by replacing the F0 Fermi integral by a Heaviside function. Considering, as a first approximation, two separated channels for front and back interface, a set of implicit equations has been established based on a single subband scheme within the Airy approach, providing a good description of surface potential, inversion charge and capacitance characteristics of FDSOI structures operated at very low temperature and for various back biases and silicon thicknesses. This analytical charge model is a first step towards a compact model of FDSOI MOSFET for circuit design at cryogenic condition.